Anion-templated assembly of a [2]catenane. - Sambrook, MR; Beer, P; Wisner, J; Paul, R; Cowley, A (2004)
The first example of a [2]catenane structure to be synthesized using anion templation is described. The nature of the anion template is demonstrated to be crucial to the assembly process, with only chloride anion producing the [2]catenane in acceptable yield. Anion binding studies reveal a dramatic catenation effect on anion selectivity properties as compared to a noncatenated acyclic receptor.